Conducting educational research : guide to completing a thesis, dissertation, or action research project - Boudah, Daniel J. (SAGE, 2020)
"Designed to be used during the research process, Conducting Educational Research: Guide for Completing a Major Project, Second Edition, walks readers through each step of a research project or thesis, including developing a research question, performing a literature search, developing a research plan, collecting and analyzing data, drawing conclusions, and sharing the conclusions with others. Throughout the book, Daniel J. Boudah covers all types of research (including experimental, descriptive, qualitative, group designs, and single subject designs) and helps readers link research questions to designs, designs to data sources and data sources to appropriate analyses. Each chapter includes activities and exercises to ensure the researcher is asking the right questions and producing a quality project"--
Terminologický slovník
Keywords: pedagogický výzkum -- metodologie; educational research -- methodology; příručky; handbooks and manuals